2022
DOI: 10.3389/fmicb.2021.817815
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Assemblies of All Xanthomonas translucens Pathotype Strains Reveal Three Genetically Distinct Clades

Abstract: The Xanthomonas translucens species comprises phytopathogenic bacteria that can cause serious damage to cereals and to forage grasses. So far, the genomic resources for X. translucens were limited, which hindered further understanding of the host–pathogen interactions at the molecular level and the development of disease-resistant cultivars. To this end, we complemented the available complete genome sequence of the X. translucens pv. translucens pathotype strain DSM 18974 by sequencing the genomes of all the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Strains AmX2 T , FX1 and FX4 T were distinct from other clade I xanthomonads such as the non-pathogenic species X. sontii that was isolated from healthy basmati rice (Oryza sativa) seeds [33]. Strains FX1 and FX4 T were clustered in a monophyletic clade closely related to, but still distinct from, the cereal pathogen X. translucens [34]. Strain AmX2 T was also distinct from the closest neighbour species, i.e.…”
mentioning
confidence: 94%
“…Strains AmX2 T , FX1 and FX4 T were distinct from other clade I xanthomonads such as the non-pathogenic species X. sontii that was isolated from healthy basmati rice (Oryza sativa) seeds [33]. Strains FX1 and FX4 T were clustered in a monophyletic clade closely related to, but still distinct from, the cereal pathogen X. translucens [34]. Strain AmX2 T was also distinct from the closest neighbour species, i.e.…”
mentioning
confidence: 94%
“…Xtt is classified in the genomic subgroup Xt-I (Sapkota et al 2020; Goettelmann et al 2022), which also includes wheat and barley-infecting Xtu. Xtt was historically divided into three groups (A, B and C) according to multilocus sequencing analysis (MLSA) of four housekeeping genes (Curland et al 2018).…”
mentioning
confidence: 99%
“…Xanthomonas translucens pv. pistaciae was isolated from the dicot pistachio, but recent genetic analysis demonstrated that this pathovar spans multiple genetic groups (Goettelmann et al 2022;Giblot-Ducray et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts in genome sequencing and phylogenomic analysis have allowed the reclassification of X. translucens based on evolutionary relationships into three genomic groups I-III (Heiden et al 2022;Goettelmann et al 2022;Sapkota et al 2020). Cereal-infecting pathovars (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation